ENGLISH-THE THEORIES OF SCHOLARS OF PAKISTAN AND INDIA ON LATEST DEVELOPMENTS IN THE METHODS OF CONTINUAL OF HUMAN LINEAGE. - Abdul Hai Madni; Muhammad Anas Muhammad Shoaib; Bashir Rehman Hanif (دی اسکالر)
This paper discusses the different theories by scholars from the countries of Pakistan and India on the subject of new advancements in medical science in the field of genealogy and the methods used to procreate in order to ensure the survival and continuation of the human race. Due to technology in modern times, many questions arise when science is used in a natural process and as such Muslim scholars have to consider many factors before making a decision. This article deals with the scholarly struggles of jurists of sub-continent in this field.